Billing Risk Handling Based on Economic Learning Material Development Model Using FMEA and RCA Methods - Sibarani, Yusuf Maruli; Imroh, Tukhas Shilul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to describe the Billing Risk Handling-Based Economic Learning Material Development Model Using the FMEA and RCA Methods. The design and research approach in this study is quantitative where quantitative research is a data collection technique that is answered objectively in strengthening the questionnaire. The results of the study show that: (1) The model for developing economic learning materials can be done using Project Based Learning. Where this model prioritizes project-based economic learning. The project in question is to use the FMEA and RCA methods in the company. (2) SOPs in the company have been prepared properly, from 7 days before the due date to more than 60 days late. However, the field conditions that occurred were not by the existing SOP, resulting in various problems. (3) Factors that become obstacles in the billing process include: it is difficult to contact corporations, which results in unscheduled payments and miss communication with clients. (4) Efforts to improve performance in the billing process are carried out by adding a computerized system, setting procedural operational standards, making KPIs (key performance indicators) on billing, making initial agreements with clients regarding late fees and offering early payments, making billing priority lists, and periodically billing blasts via WA.